Adult-onset leukodystrophies: a practical guide, recent treatment updates, and future directions - Muthusamy, Karthik; Sivadasan, Ajith; Dixon, Luke; Sudhakar, Sniya; Thomas, Maya; Danda, Sumita; Wszolek, Zbigniew K.; Wierenga, Klaas; Dhamija, Radhika; Gavrilova, Ralitza (Frontiers in Neurology, 2023)
Adult-onset leukodystrophies though individually rare, are not uncommon. This group includes several disorders that are specific for an isolated adult presentation, and several childhood leukodystrophies with attenuated phenotypes that present at a later age. Misdiagnoses occur often due to the clinical and radiological overlap with common acquired disorders like infectious, immune, inflammatory, vascular, metabolic and toxic etiologies. Prevalence of non-specific white matter changes are higher in this population, that poses challenges during diagnostic consideration. Clinico-radiological spectrum and molecular landscape has not been completely elucidated at this time. The approach to adult-onset leukodystrophies is less well standardized when compared to the childhood counterpart. Absence of family history and reduced penetrance in certain disorders often create dilemma. Comprehensive evaluation and molecular confirmation when available help in prognostication, early initiation of treatment when available, enrollment in clinical trials, and provides valuable information for the family with regards to reproductive counselling. It this article, we aim to formulate an approach to adult-onset leukodystrophies that would be useful in routine practice, discuss common adult-onset leukodystrophies with usual and unusual presentations, neuroimaging findings, recent advances in treatment, acquired mimics, and provide an algorithm for comprehensive clinical, radiological, and genetic evaluation that would facilitate early diagnosis and consider active treatment options when available. High index of suspicion, awareness of the clinico-radiological presentations, and comprehensive genetic evaluation is paramount as treatment options are available for several disoders when diagnosed early in the disease course.